A study on the implementation fidelity of the performance-based financing policy in Burkina Faso after 12 months - Oriane Bodson; Ahmed Barro; Anne-Marie Tu; Nestor Zanté; Paul-André Somé; Valéry Ridde (BMC, 2018)
Abstract Background Performance-based financing (PBF) in the health sector has recently gained momentum in low- and middle-income countries (LMICs) as one of the ways forward for achieving Universal Health Coverage. The major principle underlying PBF is that health centers are remunerated based on the quantity and quality of services they provide. PBF has been operating in Burkina Faso since 2011, and as a pilot project since 2014 in 15 health districts randomly assigned into four different models, before an eventual scale-up. Despite the need for expeditious documentation of the impact of PBF, caution is advised to avoid adopting hasty conclusions. Above all, it is crucial to understand why and how an impact is produced or not. Our implementation fidelity study approached this inquiry by comparing, after 12 months of operation, the activities implemented against what was planned initially and will make it possible later to establish links with the policy's impacts. Methods Our study compared, in 21 health centers from three health districts, the implementation of activities that were core to the process in terms of content, coverage, and temporality. Data were collected through document analysis, as well as from individual interviews and focus groups with key informants. Results In the first year of implementation, solid foundations were put in place for the intervention. Even so, implementation deficiencies and delays were observed with respect to certain performance auditing procedures, as well as in payments of PBF subsidies, which compromised the incentive-based rationale to some extent. Conclusion Over next months, efforts should be made to adjust the intervention more closely to context and to the original planning.